Tinjauan Yuridis Akibat Hukum Terhadap Debitur Atas Gugatan Eror In Persona Yang Diajukan Kepada Kreditur - Purba, Masni; Habeahan, Besty (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the regulation of error in persona lawsuits in Indonesian civil law and its impact on debtors in the judicial process. The results of this study show that an error in persona lawsuit can be the basis for the defendant to object to formal defects in the lawsuit filed by the plaintiff. This formal defect can be in the form of errors in the determination of the parties involved in the case, vagueness in the formulation of the lawsuit, or violation of the provisions of procedural law. The legal consequence of an error in persona lawsuit is that the lawsuit can be declared inadmissible. This has significant implications for debtors, as it can hamper creditors' efforts to collect debts and provide legal protection for innocent debtors. This research concludes that it is important for parties involved in civil cases to understand the concept of error in persona and pay attention to formal aspects in the preparation of lawsuits so that the judicial process can run effectively and efficiently.